Site controlled red-yellow-green light emitting InGaN quantum discs on nano-tipped GaN rods. Issue 21 (13th May 2016) - Conroy, M.; Li, H.; Kusch, G.; Zhao, C.; Ooi, B.; Edwards, P. R.; Martin, R. W.; Holmes, J. D.; Parbrook, P. J.
Abstract : Utilising the "space-filling/self-limiting" epitaxial growth mechanism we present a method of producing coalescence free wafer scale ultra-high density gan nanorod templates for site controlled growth of red-yellow-green light emitting ingan quantum discs. Abstract : We report a method of growing site controlled InGaN multiple quantum discs (QDs) at uniform wafer scale on coalescence free ultra-high density (>80%) nanorod templates by metal organic chemical vapour deposition (MOCVD). The dislocation and coalescence free nature of the GaN space filling nanorod arrays eliminates the well-known emission problems seen in InGaN based visible light sources that these types of crystallographic defects cause. Correlative scanning transmission electron microscopy (STEM), energy-dispersive X-ray (EDX) mapping and cathodoluminescence (CL) hyperspectral imaging illustrates the controlled site selection of the red, yellow and green (RYG) emission at these nano tips. This article reveals that the nanorod tips' broad emission in the RYG visible range is in fact achieved by manipulating the InGaN QD's confinement dimensions, rather than significantly increasing the In%. This article details the easily controlled method of manipulating the QDs dimensions producing high crystal quality InGaN without complicated growth conditions needed for strain relaxation and alloy compositional changes seen for bulk planar GaN templates.